Preparation method of concrete mixture water molecule migration inhibitor

By using a combination of dextran gel, xanthan gum and modified sodium alginate microspheres in concrete, the migration of water molecules is inhibited, the apparent quality and durability of concrete are solved, and the compressive strength is achieved and lower water discharge rate.

CN119461941APending Publication Date: 2025-02-18SHANDONG SHITONG HIGHWAY CONSTR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411623063.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In bridge concrete construction, apparent quality problems such as water marks, color difference, black spots, and sand lines often appear on the concrete surface, resulting in the impact of structural durability. When the amount of existing water-retaining components such as cellulose ethers and biopolysaccharides are too high, the concrete viscosity will be too large and affect construction.

Method used

Using a concrete mixture water molecular migration inhibitor, the composite solution is formed by combining dextran gel and xanthan gum with modified sodium alginate microspheres, and high-speed stirring and shear thinning effects are used to form a high-speed Flowing liquid, inhibits water molecules migration.

Benefits of technology

The migration of water molecules inside the concrete is effectively controlled, the water excretion rate and pressure excretion rate are reduced, the compressive strength and durability of the concrete are improved, and the apparent quality is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005133959320000091
    Figure BDA0005133959320000091
Patent Text Reader

Abstract

The invention discloses a preparation method of a concrete mixture water molecule migration inhibitor. The preparation method comprises the following steps: (1) mixing sephadex and xanthan gum, weighing the mixture, adding the mixture into an aqueous solution of phosphate, and stirring until the mixture is completely dissolved to form a water-retaining solution; (2) weighing a water-retaining solution, putting the water-retaining solution into a stirring device, increasing the rotating speed to be not less than 6000 r / min, slowly adding the modified sodium alginate microspheres, uniformly stirring, extracting the modified sodium alginate microspheres from the stirring device, and standing until the solution is stable to form a concrete mixture water molecule migration inhibitor; the modified sodium alginate microspheres take magnesium hydroxide as a porous structure, and pores are filled with sodium alginate and magnesium sulfate. By adopting the inhibitor, approximate laminar motion is controlled in the early stage of mixture coagulation, diffusion motion is controlled in the later stage of coagulation, internal free water is effectively controlled to excessively migrate to the surface, and adverse effects of migration of water molecules on concrete strength and apparent quality are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete admixtures, and in particular to a method for preparing a water molecule migration inhibitor for concrete mixtures. Background Art

[0002] At present, in the process of bridge concrete construction, obvious surface quality defects such as color difference, water temperature, black spots, sand lines, etc. often occur, which not only affect the appearance, but also affect the durability of the concrete structure. Therefore, it is very important to improve the surface quality of concrete. In concrete construction, especially the concrete pumping construction process requires concrete to have greater fluidity, and the free water content in high-fluidity concrete increases. Some free water migrates to the surface of the concrete in the fresh concrete to form normal pressure bleeding, which affects the workability of the concrete; some free water migrates to the side surface of the concrete structure after the concrete is poured but before it solidifies to form pressure bleeding, resulting in obvious water lines, color difference, black spots, sand lines and other surface quality problems after the concrete solidifies.

[0003] Studies have shown that the distribution of moisture in concrete is uneven, the moisture content shows a regularity of decreasing over time, and its internal distribution also changes from uneven to uniform over time. The moisture changes in concrete materials are mainly caused by hydration reaction, evaporation and internal moisture self-migration. As the two most important processes of moisture change, evaporation and hydration both show certain regularity, and the increase in evaporation will reduce the final hydration amount to a certain extent. At the same time, under the combined effect of these three processes, fresh concrete has a very obvious surface effect in the evolution process: the internal moisture is a monotonically decreasing pattern, but the surface moisture in different environments will increase first and then decrease over time in mild environments, and directly decrease in harsh environments, so the surface concrete performance is completely different. The change in the surface moisture state directly affects the hydration degree and workability of the surface, thereby directly affecting the interlayer bonding performance of layered concrete. The migration of moisture in concrete is mainly approximate laminar flow and diffusion movement, which become the dominant movements of moisture migration in the early and late stages of setting after mixing respectively: the upward migration of moisture in concrete in the early stage is caused by the different densities of water and solid matter; the migration of moisture in concrete in the later stage is mainly caused by the gradient difference caused by the uneven distribution of moisture content.

[0004] In order to improve the apparent quality of concrete and improve the problem of concrete bleeding and segregation, it is mainly adjusted by adding water-retaining components. Commonly used water-retaining components include cellulose ethers, biopolysaccharides, etc. Cellulose ethers reduce free water in the slurry by absorbing free water by themselves, thereby reducing the phenomenon of bleeding and segregation. Biopolysaccharides mainly reduce bleeding and segregation by binding free water through intermolecular bridging. However, cellulose ethers are highly sensitive and have poor effects at low dosages. Increased dosages cause fluidity to decrease too quickly. Therefore, the use of biopolysaccharide water-retaining components such as xanthan gum and Wenlun gum is a new choice for improving concrete bleeding and segregation. However, although xanthan gum and Wenlun gum are not highly sensitive, excessive dosages will cause excessive viscosity of the concrete mixture, which will have an adverse effect on the concrete. Especially in large-volume concrete, the pressure of the concrete slurry poured in the lower layer will be too high during the construction process, so that the free water bound by the bridging effect migrates to the concrete surface under high pressure or vibration, forming a connecting channel inside and bleeding outside, which has an adverse effect on the concrete. Therefore, the use of water-retaining components alone cannot effectively control water migration, especially in large-volume concrete construction, and the effect of improving the pressure water bleeding rate is limited. Therefore, it is very necessary to explore technical measures to avoid water migration inside concrete, achieve reasonable control of water molecules inside concrete mixtures, reduce its water bleeding rate, improve workability and enhance surface quality. Summary of the invention

[0005] In view of the problems existing in the above-mentioned background technology, the present invention prepares a concrete mixture water molecule migration inhibitor, which is used to control the approximate laminar flow motion in the early stage of solidification and the diffusion motion in the later stage of solidification, thereby effectively controlling the excessive migration of internal free water to the surface and avoiding the adverse effects of water molecule migration on the strength and apparent quality of concrete.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] A method for preparing a concrete mixture water molecule migration inhibitor comprises the following steps:

[0008] (1) After mixing the dextran gel and xanthan gum, weigh the mixture, add it into the phosphate aqueous solution and stir until it is completely dissolved to form a water retention solution;

[0009] (2) Weigh the water retention solution and put it into a stirring device, increase the speed to not less than 6000 r / min, slowly add the modified sodium alginate microspheres, stir evenly, remove the stirring device, and let it stand until the solution is stable to form a concrete mixture water molecule migration inhibitor;

[0010] In step (1), the mass ratio of the mixture of glucan gel and xanthan gum to the aqueous solution of phosphate is 1:100, the mass ratio of the glucan gel and xanthan gum is 1:3-5, and the mass ratio of phosphate to water in the aqueous solution of phosphate is 0.01-0.03:100;

[0011] The mass ratio of the water retention solution to the modified sodium alginate microspheres in step (2) is 100:10-15;

[0012] The modified sodium alginate microspheres have a porous structure of magnesium hydroxide, and the pores are filled with sodium alginate and magnesium sulfate.

[0013] Furthermore, the phosphate of the present invention is selected from sodium hexametaphosphate [(NaPO3)6], sodium tripolyphosphate (Na5P3O 10 )

[0014] Furthermore, the method for preparing the modified sodium alginate microspheres of the present invention comprises the following steps:

[0015] (1) uniformly mixing a surfactant, a co-surfactant and an oil phase to form an oil phase solution; uniformly mixing magnesium sulfate and sodium alginate I and adding the mixture into water to form an aqueous phase solution A; uniformly mixing an alkaline solution and sodium alginate II and dissolving the mixture to form an aqueous phase solution B;

[0016] The mass ratio of the surfactant, the co-surfactant and the oil phase is 1:2-4:30-50;

[0017] The mass ratio of the mixture of magnesium sulfate and sodium alginate I to water in the aqueous phase solution A is 30:100, and the mass ratio of magnesium sulfate to sodium alginate I is 2:1-2;

[0018] The mass ratio of the alkaline solution to sodium alginate II in the aqueous phase solution B is 100:3-5; the alkaline solution is a sodium hydroxide solution or concentrated ammonia water, the mass concentration of the sodium hydroxide solution is 35%-40%, and the mass concentration of the concentrated ammonia water is 22%-28%;

[0019] (2) slowly dropping 50 parts by weight of aqueous solution A into 100 parts by weight of the oil phase solution and stirring continuously to form an emulsion I, slowly dropping 10 parts by weight of aqueous solution B into another 100 parts by weight of the oil phase solution and stirring continuously to form an emulsion II, slowly dropping the emulsion II into the emulsion I, stirring evenly, reacting for 8 to 12 hours, filtering to remove the liquid phase, and ultrasonically washing the non-liquid phase material with anhydrous ethanol for multiple times to obtain the modified sodium alginate microspheres;

[0020] Furthermore, the surfactant of the present invention is selected from any one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and polyethylene glycol octylphenyl ether.

[0021] Furthermore, the co-surfactant of the present invention is selected from any one of n-butanol and n-pentanol or a mixture of the two in any proportion.

[0022] Furthermore, the oil phase of the present invention is selected from any one of cyclohexane and n-heptane or a mixture of the two in any proportion.

[0023] Furthermore, the present invention also provides the concrete mixture water molecule migration inhibitor used in the concrete mixture, and the amount of the water molecule migration inhibitor added is 0.01-0.10% of the mass of the cementitious material.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The water molecule migration inhibitor prepared by the present invention first forms a microsphere structure using magnesium sulfate and sodium alginate by a W / O emulsion method, wherein the hard structure of the microsphere structure is magnesium hydroxide and the flexible network is sodium alginate. That is, a microsphere structure is formed in which magnesium hydroxide is a porous structure and the pores are filled with sodium alginate. At the same time, due to the relatively high magnesium sulfate content, a large amount of unreacted magnesium sulfate is adsorbed in the pores.

[0026] (2) The modified sodium alginate micro-nano structure formed above is mixed with a composite solution of xanthan gum and glucan gel, and the composite aqueous solution of xanthan gum and glucan gel is firstly rotated at high speed to cause a shear thinning effect to occur in the composite aqueous solution, thereby forming a highly fluid liquid; secondly, after being evenly dispersed, the stirring is quickly stopped to cause the xanthan gum composite solution to reversely thicken, thereby ensuring that the micro-nano structure remains in a relatively stable state in the solution and does not precipitate.

[0027] (3) When the water molecule migration inhibitor prepared by the present invention is added to the concrete mixture, the outer layer of xanthan gum absorbs water first, and at the same time, a large amount of free water is bound by the bridging effect generated by the xanthan gum, thereby reducing the separation of bleeding water; at the same time, the free water bound by the xanthan gum further increases the dissolution of magnesium sulfate, magnesium hydroxide, and sodium alginate in the microspheres. In particular, the further dissolution of sodium alginate greatly increases the viscosity of the entire structure. The higher the pH value, the greater the swelling, the stronger the water absorption, and the stronger the adhesion, that is, the mutual adhesion between particles and molecules. This improves the water retention stability of xanthan gum and effectively prevents the internal interlayer water of the concrete from overflowing to form bleeding water. In this process, a large amount of divalent magnesium ions and sulfate ions are dissolved in magnesium sulfate, so that calcium ions are directly formed into calcium sulfate when they approach, thereby effectively preventing the calcium ions from reacting with sodium alginate to form gel.

[0028] Xanthan gum has the ability to chelate calcium ions, so the structure of xanthan gum wrapped sodium alginate microspheres can block the calcium ions generated during the concrete hydration process between the xanthan gum molecular structure through its own chelating ability for calcium ions, thus avoiding the gelation and loss of viscosity of sodium alginate. At the same time, in order to improve the chelating ability of calcium ions, phosphate solution is added on the basis of xanthan gum to improve the calcium chelating ability of the entire water molecule migration inhibitor system, but in order to avoid the adverse effect of its slow setting effect on cement hydration, its dosage needs to be significantly controlled. The beaded dextran gel absorbs water with its extremely high hydrophilicity to form a swollen gel, which can achieve higher flow properties under pressure, can not only absorb water, but also fill tiny gaps in concrete. Compared with xanthan gum and calcium alginate, its water absorption is not affected under pressure, and it can serve as an important auxiliary role for calcium alginate and xanthan gum to absorb and retain water.

[0029] (4) The water molecule migration inhibitor of the present invention acts during the construction and vibration molding of large-volume concrete. In the early stage of the whole process, the modified sodium alginate microspheres form a semi-embedded form for sodium alginate and magnesium sulfate, reducing their outward migration rate. After the porous structure releases sodium alginate and magnesium sulfate in the later stage, its porous structure has water absorption, absorbs water and controls water migration, and plays an internal curing role in the later stage of cement reaction. At the same time, the magnesium hydroxide part will participate in the cement hydration reaction to form a micro-expansion structure, reducing the shrinkage of concrete. At the same time, since the magnesium hydroxide is mainly constrained in the water molecule migration channel, it can react with the infiltrated carbon dioxide to block the pores and improve the concrete's anti-carbonation ability.

[0030] In summary, through the synergistic effect of different components, the migration of internal water molecules is effectively controlled, the active regulation of internal water molecules is achieved, the water segregation and pressure water bleeding rate are reduced, the compressive strength of concrete is improved, the shrinkage rate is reduced, and the durability of concrete is improved. DETAILED DESCRIPTION

[0031] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention may be implemented in many different forms, and the present invention should not be construed as being limited to the specific embodiments set forth herein. On the contrary, these embodiments are provided to explain the principles of the present invention and their practical applications, so that other persons skilled in the art can understand the various embodiments of the present invention and the various modifications suitable for specific intended applications.

[0032] The parts of each component in each example are in parts by mass.

[0033] The reference concrete used in the following embodiments and comparative examples is the concrete with the proportion described in the blank example.

[0034] Blank example

[0035] The original concrete mix is ​​shown in Table 1. Cement, Shan Aluminum P.O42.5; Grade I fly ash; Lubi S95 grade mineral powder; limestone machine-made sand MB value 0.75, fineness modulus 2.8, stone powder content 10.4%.

[0036] Table 1 Concrete mix ratio (kg / m 3 )

[0037] cement Fly ash Mineral powder sand gravel water Admixtures 330 65 45 739 1063 168 6.6

[0038] Example 1

[0039] A method for preparing a concrete mixture water molecule migration inhibitor comprises the following steps:

[0040] (1) Preparation of modified sodium alginate microspheres: sodium dodecyl sulfate, n-butanol, and cyclohexane are mixed in a mass ratio of 1:2:30 to form an oil phase solution; 30 parts of magnesium sulfate and sodium alginate are added to 100 parts of water in a mass ratio of 2:1 to form an aqueous phase solution A; 100 parts of sodium hydroxide solution (concentration of 35%) and 5 parts of sodium alginate are mixed and dissolved to form an aqueous phase solution B; 100 parts of the oil phase solution are taken, and 50 parts of the aqueous phase solution A are slowly added thereto and stirred continuously to form an emulsion I; 100 parts of the oil phase solution are taken, and 10 parts of the aqueous phase solution B are slowly added thereto and stirred continuously to form an emulsion II; emulsion II is slowly added to emulsion I, stirred uniformly, reacted for 8 hours, filtered to remove the liquid phase, and the non-liquid phase material is ultrasonically washed with anhydrous ethanol for multiple times to obtain modified sodium alginate microspheres;

[0041] (2) Mix dextran gel and xanthan gum in a mass ratio of 1:5, weigh 1 part and add it to 100 parts of sodium tripolyphosphate in an aqueous solution of solute and water in a mass ratio of 0.03:100, stir until completely dissolved, and form a water retention solution; weigh 100 parts of the water retention solution, put it into a stirring device, increase the speed to 6000 r / min, slowly add 15 parts of modified sodium alginate microspheres, stir evenly, remove the stirring device, and let it stand until the solution is stable, thereby forming an additive for controlling the migration of water molecules in concrete.

[0042] The dosage of additive is 0.04% of the amount of cementitious material.

[0043] Example 2

[0044] A method for preparing a concrete mixture water molecule migration inhibitor comprises the following steps:

[0045] (1) Preparation of modified sodium alginate microspheres: Hexadecyltrimethylammonium bromide, n-pentanol, and n-heptane are mixed in a mass ratio of 1:4:50 to form an oil phase solution; 30 parts of magnesium sulfate and sodium alginate are added to 120 parts of water in a mass ratio of 1:1 to form an aqueous solution A; 100 parts of concentrated ammonia (concentration of 28%) and 3 parts of sodium alginate are mixed and dissolved to form an aqueous solution B; 100 parts of the oil phase solution are taken, and 50 parts of the aqueous solution A are slowly added thereto and stirred continuously to form an emulsion I; 100 parts of the oil phase solution are taken, and 10 parts of the aqueous solution B are slowly added thereto and stirred continuously to form an emulsion II; emulsion II is slowly added to emulsion I, stirred uniformly, reacted for 12 hours, and then the liquid phase is removed by filtration, and the non-liquid phase material is ultrasonically washed with anhydrous ethanol for multiple times to obtain modified sodium alginate microspheres;

[0046] (2) Mix the dextran gel and xanthan gum in a mass ratio of 1:3, weigh 1 part, add it to 100 parts of an aqueous solution of phosphate solute and water in a mass ratio of 0.01:100, and stir until completely dissolved to form a water retention solution. Weigh 100 parts of the water retention solution, put it into a stirring device, increase the speed to 6800r / min, slowly add 10 parts of modified sodium alginate microspheres, stir evenly, remove the stirring device, and let it stand until the solution is stable to form an additive for controlling the migration of water molecules in concrete.

[0047] The dosage of additive is 0.04% of the amount of cementitious material.

[0048] Example 3

[0049] A method for preparing a concrete mixture water molecule migration inhibitor comprises the following steps:

[0050] (1) Preparation of modified sodium alginate microspheres: polyethylene glycol octylphenyl ether, n-butanol, and n-heptane are mixed in a mass ratio of 1:3:40 to form an oil phase solution; 30 parts of magnesium sulfate and sodium alginate are added to 110 parts of water in a mass ratio of 2:1.5 to form an aqueous phase solution A; 100 parts of sodium hydroxide solution (concentration of 40%) and 4 parts of sodium alginate are mixed and dissolved to form an aqueous phase solution B; 100 parts of the oil phase solution are taken, and 50 parts of the aqueous phase solution A are slowly added thereto and stirred continuously to form an emulsion I; 100 parts of the oil phase solution are taken, and 10 parts of the aqueous phase solution B are slowly added thereto and stirred continuously to form an emulsion II; emulsion II is slowly added to emulsion I, stirred uniformly, reacted for 10 hours, filtered to remove the liquid phase, and the non-liquid phase material is ultrasonically washed with anhydrous ethanol for multiple times to obtain modified sodium alginate microspheres;

[0051] (2) Mix the dextran gel and xanthan gum in a mass ratio of 1:4, weigh 1 part, add it to 100 parts of an aqueous solution of sodium hexametaphosphate and water in a mass ratio of 0.02:100, stir until completely dissolved, and form a water retention solution. Weigh 100 parts of the water retention solution, put it into a stirring device, increase the speed to 6500r / min, slowly add 12 parts of modified sodium alginate microspheres, stir evenly, remove the stirring device, and let it stand until the solution is stable, thereby forming an additive for controlling the migration of water molecules in concrete.

[0052] The dosage of additive is 0.04% of the amount of cementitious material.

[0053] Comparative Example 1

[0054] The difference from Example 3 is that the magnesium hydroxide microspheres are not combined with sodium alginate, that is, the sodium alginate is removed in step (1), and the other substances are reacted to form magnesium hydroxide microspheres, which are then mixed with sodium alginate and added to step (2).

[0055] The dosage of additive is 0.04% of the amount of cementitious material.

[0056] Comparative Example 2

[0057] The difference from Example 3 is that no microspheres are prepared, and a solution formed by mixing magnesium sulfate, sodium alginate, xanthan gum, dextran gel and phosphate is added to concrete as an additive.

[0058] The dosage of additive is 0.04% of the amount of cementitious material.

[0059] Comparative Example 3

[0060] The difference from Example 3 is that a polymer inert microsphere structure is used, magnesium sulfate is not added to prepare the microspheres, and the polymer inert microspheres are added together with sodium alginate to prepare the additive in step (2).

[0061] The dosage of additive is 0.04% of the amount of cementitious material.

[0062] Comparative Example 4

[0063] Compared with Example 3, the difference is that the microspheres are prepared by using magnesium sulfate and sodium alginate in a mass ratio of 0.5:1.

[0064] The dosage of additive is 0.04% of the amount of cementitious material.

[0065] Comparative Example 5

[0066] Compared with Example 3, the difference is that the microspheres are prepared by using magnesium sulfate and sodium alginate in a mass ratio of 4:1.

[0067] The dosage of additive is 0.04% of the amount of cementitious material.

[0068] Comparative Example 6

[0069] Compared with Example 3, the difference is that the microspheres are prepared by using magnesium sulfate and sodium alginate in a mass ratio of 2:0.5.

[0070] The dosage of additive is 0.04% of the amount of cementitious material.

[0071] Comparative Example 7

[0072] Compared with Example 3, the difference is that the microspheres are prepared by using magnesium sulfate and sodium alginate in a mass ratio of 2:4.

[0073] The dosage of additive is 0.04% of the amount of cementitious material.

[0074] Comparative Example 8

[0075] Compared with Example 3, the difference is that after the dextran gel and xanthan gum are mixed at a ratio of 1:4 and 1 part is added, an additional 0.5 part of xanthan gum is added.

[0076] The dosage of additive is 0.04% of the amount of cementitious material.

[0077] Comparative Example 9

[0078] Compared with Example 3, the difference is that after the glucan gel and xanthan gum are mixed in 0.5 parts, the xanthan gum is 0.3 parts and the glucan is 0.2 parts.

[0079] The dosage of additive is 0.04% of the amount of cementitious material.

[0080] Comparative Example 10

[0081] The difference from Example 3 is that no dextran gel is added.

[0082] The dosage of additive is 0.04% of the amount of cementitious material.

[0083] Comparative Example 11

[0084] The difference from Example 3 is that the amount of xanthan gum added is 0.8 parts, and the amount of dextran gel added is 0.6 parts.

[0085] The dosage of additive is 0.04% of the amount of cementitious material.

[0086] Comparative Example 12

[0087] The difference from Example 3 is that no phosphate is added.

[0088] The dosage of additive is 0.04% of the amount of cementitious material.

[0089] Comparative Example 13

[0090] The difference from Example 3 is that the mass ratio of the added phosphate to water is 0.2:100.

[0091] The dosage of additive is 0.04% of the amount of cementitious material.

[0092] Comparative Example 14

[0093] The difference from Example 3 is that the modified sodium alginate microspheres and xanthan gum are added separately, that is, step (2) is not performed.

[0094] The dosage of additive is 0.04% of the amount of cementitious material.

[0095] The concrete properties obtained in the above embodiments and comparative examples are shown in Table 2.

[0096] Table 2 Concrete properties of various embodiments and comparative examples

[0097]

[0098] From the data in Table 2, we can find that:

[0099] Compared with Example 3, Comparative Example 1 has a water bleeding rate of 0, but the pressure water bleeding rate, surface pore area ratio and shrinkage rate are all increased; the compressive strength is decreased. This shows that sodium alginate lacks the protection of the high magnesium ion concentration microsphere structure formed by magnesium hydroxide and magnesium sulfate, and fails to form an internal and external embedded structure with xanthan gum. It is easy to react quickly with the calcium ions produced during the cement hydration reaction to form calcium alginate. Although a large amount of absorbed water reduces the concrete water bleeding rate, once under pressure conditions, the structure collapses, releasing a large amount of water, causing the pressure water bleeding rate to increase, and then the compressive strength decreases, and the shrinkage rate increases. In particular, the control effect of high concentration magnesium ions is lacking, the gel formed by sodium alginate is faster, the process is uncontrollable, and flaky and miniaturized appear, the viscosity is reduced, and the overall water retention is reduced. This also proves that the microspheres are crucial to the binding and targeted control of sodium alginate.

[0100] Compared with Example 3, the water bleeding rate of Comparative Example 2 is 0, but the pressure water bleeding rate, surface pore area ratio and shrinkage rate are all increased; the compressive strength is decreased. Compared with Comparative Example 1, the pressure water bleeding rate, surface pore area ratio, shrinkage rate and compressive strength are all deteriorated, which shows that not only the same reason as in Comparative Example 1 causes the concrete performance to decline, but also because the porous microsphere structure is not formed (the porous microsphere structure can penetrate and absorb water under high pressure), resulting in an increase in water bleeding and a decrease in strength. However, due to the high content of magnesium sulfate, the volume expands, thereby reducing the shrinkage rate, but the excessive magnesium sulfate causes uneven changes in the internal and external structures, resulting in poor volume stability, so although the shrinkage rate is reduced, the compressive strength is also significantly reduced.

[0101] Compared with Example 3, the pressure water seepage rate of the concrete increased, the shrinkage rate increased, the compressive strength decreased, and the surface pores increased in Comparative Example 3. This shows that the composite structure of the microsphere structure formed by magnesium ions and magnesium oxides and sodium alginate has the effect of significantly reducing pressure water seepage, improving compressive strength, and reducing shrinkage.

[0102] Compared with Example 3, the pressure water bleeding rate of Comparative Example 4 increased, the surface pore area increased, the 28d compressive strength decreased, and the shrinkage rate increased. This is mainly because the magnesium sulfate content is low, the number of microspheres formed is low, and the magnesium sulfate is completely consumed, the magnesium ion content in the additive is low, the protective effect on sodium alginate is low, and sodium alginate reacts too quickly with calcium ions, which affects the pressure water bleeding rate, and then affects the surface pore area, compressive strength and shrinkage rate.

[0103] Compared with Example 3, Comparative Example 5 has little difference in other performance indicators except that the compressive strength is significantly reduced; compared with Comparative Example 4, its shrinkage rate is reduced, the pressure water bleeding rate is reduced, but the compressive strength is reduced. This is mainly because the magnesium sulfate content is increased, and there is an excessively high concentration of magnesium ions in the solution, which has a sufficient protective effect on sodium alginate, preventing sodium alginate from reacting too quickly with calcium ions, so that the pressure water bleeding rate is reduced, but the magnesium ion content is too high, which is prone to expansion and cracking, resulting in an uneven internal structure, so the compressive strength is reduced.

[0104] Compared with Example 3, the pressure water seepage rate of Comparative Example 6 increased and the compressive strength decreased. The main reason is that the dosage of sodium alginate is too low, resulting in a decrease in the viscosity effect of the water-retaining structure formed by the xanthan gum after the addition of the additive, resulting in an increase in the water release of xanthan gum under high pressure conditions and an increase in the pressure water seepage rate.

[0105] The compressive strength of Comparative Example 7 is significantly reduced compared with Example 3. This indicates that excessive sodium alginate will have an adverse effect on the mechanical properties of concrete.

[0106] Compared with Example 3, the pressure bleeding rate of Comparative Example 8 is improved, the pore area is increased, and the 28d compressive strength is reduced. This is mainly because excessive xanthan gum causes the viscosity of the concrete to increase, the state of the mixture to decrease, resulting in problems such as non-compactness in vibration, increased surface defects, increased internal defects, and decreased strength. In addition, the concentration of xanthan gum is relatively increased, which easily causes phase separation between sodium alginate and xanthan gum, thereby facilitating further formation of gel by sodium alginate, while reducing its viscosity effect, so that its pressure bleeding rate is improved.

[0107] Compared with the benchmark concrete, the performance of Comparative Example 9 is improved, but compared with Example 3, the performance is reduced. This is because the xanthan gum dosage is too low and the water retention is insufficient, resulting in increased water bleeding rate and pressure water bleeding rate, which in turn has an adverse effect on strength and volume stability.

[0108] Compared with the benchmark concrete, the performance of Comparative Example 10 is improved, but compared with Example 3, the performance is all decreased. In particular, the pressure water seepage rate increases too fast, resulting in an increase in surface pores and an increase in shrinkage. This shows that the water absorption and water retention of the polysaccharide gel is crucial for the improvement of concrete performance. The polysaccharide gel with a beaded structure absorbs water with its extremely high hydrophilicity to form a swollen gel, which has lubricity under pressure and can achieve higher flow properties, which can not only achieve the absorption of water, but also achieve the filling of tiny gaps in concrete. Compared with xanthan gum and calcium alginate, its water absorption under pressure is not affected, and it can be used as an important auxiliary role for calcium alginate and xanthan gum to absorb and retain water.

[0109] Compared with Example 3, the pore area of ​​Comparative Example 11 increased and the 28d compressive strength decreased. This was mainly because the excessive amount of glucan gel increased the viscosity of the concrete, the state of the mixture decreased, and the vibration was not dense, the surface defects increased, the internal defects increased, and the strength decreased.

[0110] Compared with Example 3, the pressure water bleeding rate of Comparative Example 12 increases. This is mainly because phosphate mainly chelates calcium ions, avoids premature and rapid reaction with sodium alginate, reduces its viscosity, and causes water retention structure destruction under high pressure conditions to cause water bleeding. Insufficient phosphate causes insufficient chelated calcium ions, which causes sodium alginate to react with calcium ions prematurely, resulting in decreased viscosity, increased elastic effect, decreased water retention under pressure conditions, increased pressure water bleeding rate, decreased compressive strength, and increased shrinkage.

[0111] Compared with Example 3, the compressive strength of Comparative Example 13 decreased significantly and the shrinkage increased. This is mainly because phosphate mainly chelates calcium ions, and excessive addition causes slow cement hydration, which in turn affects the compressive strength. In addition, during the reaction process, the water retention effect of xanthan gum gradually disappears, and due to the slow hydration reaction, free water increases, excessive evaporation, and shrinkage increases. Therefore, the phosphate dosage should be controlled to avoid the adverse effects of its retarding effect.

[0112] Compared with Example 3, Comparative Example 14 has an increased pressure water bleeding rate, a decreased compressive strength, and an increased shrinkage rate. This shows that the modified sodium alginate-magnesium hydroxide microspheres are compounded with xanthan gum to form an embedding structure, which can achieve a targeted synergistic effect of water retention and viscosity increase of sodium alginate and xanthan gum, and improve the improvement effect on concrete performance. If the two are separated, the synergistic water retention and viscosity increase effect is limited, which increases the pressure water bleeding rate and the shrinkage rate.

Claims

1. A method for preparing a concrete mixture water molecule migration inhibitor, characterized in that: The steps include: (1) After mixing the dextran gel and xanthan gum, weigh the mixture, add it into the phosphate aqueous solution and stir until it is completely dissolved to form a water retention solution; (2) Weigh the water retention solution and put it into a stirring device, increase the speed to not less than 6000 r / min, slowly add the modified sodium alginate microspheres, stir evenly, remove the stirring device, and let it stand until the solution is stable to form a concrete mixture water molecule migration inhibitor; The modified sodium alginate microspheres have a porous structure of magnesium hydroxide, and the pores are filled with sodium alginate and magnesium sulfate.

2. The method for preparing a concrete mixture water molecule migration inhibitor according to claim 1, characterized in that: In the preparation process of the concrete mixture water molecule migration inhibitor, the mass ratio of the mixture of glucan gel and xanthan gum to the phosphate aqueous solution in step (1) is 1:100, the mass ratio of the glucan gel and xanthan gum is 1:3-5, and the mass ratio of phosphate to water in the phosphate aqueous solution is 0.01-0.03:100; The mass ratio of the water retention solution to the modified sodium alginate microspheres in step (2) is 100:10-15.

3. The method for preparing a concrete mixture water molecule migration inhibitor according to claim 2, characterized in that: The phosphate is selected from any one of sodium hexametaphosphate and sodium tripolyphosphate.

4. The method for preparing a concrete mixture water molecule migration inhibitor according to any one of claims 1 to 3, characterized in that: The preparation method of the modified sodium alginate microspheres comprises the following steps: (1) uniformly mixing a surfactant, a co-surfactant and an oil phase to form an oil phase solution; uniformly mixing magnesium sulfate and sodium alginate I and adding the mixture into water to form an aqueous phase solution A; uniformly mixing an alkaline solution and sodium alginate II and dissolving the mixture to form an aqueous phase solution B; (2) Slowly drop 50 parts by weight of aqueous solution A into 100 parts by weight of the oil phase solution and stir continuously to form emulsion I, slowly drop 10 parts by weight of aqueous solution B into another 100 parts by weight of the oil phase solution and stir continuously to form emulsion II, slowly drop emulsion II into emulsion I, stir evenly, react for 8 to 12 hours, filter out the liquid phase, and ultrasonically wash the non-liquid phase material with anhydrous ethanol for multiple times to obtain the modified sodium alginate microspheres.

5. The method for preparing a concrete mixture water molecule migration inhibitor according to claim 4, characterized in that: In the preparation method of the modified sodium alginate microspheres, the mass ratio of the surfactant, the co-surfactant and the oil phase in step (1) is 1:2-4:30-50; The mass ratio of the mixture of magnesium sulfate and sodium alginate I to water in the aqueous phase solution A is 30:100, and the mass ratio of magnesium sulfate to sodium alginate I is 2:1-2; The mass ratio of the alkaline solution to sodium alginate II in the aqueous phase solution B is 100:3-5; the alkaline solution is a sodium hydroxide solution or concentrated ammonia water, the mass concentration of the sodium hydroxide solution is 35%-40%, and the mass concentration of the concentrated ammonia water is 22%-28%.

6. The method for preparing a concrete mixture water molecule migration inhibitor according to claim 5, characterized in that: The surfactant is selected from any one of sodium dodecyl sulfate, hexadecyl trimethyl ammonium bromide and polyethylene glycol octyl phenyl ether.

7. The method for preparing a concrete mixture water molecule migration inhibitor according to claim 5, characterized in that: The auxiliary surfactant is selected from any one of n-butanol and n-pentanol or a mixture of the two in any proportion.

8. The method for preparing a concrete mixture water molecule migration inhibitor according to claim 5, characterized in that: The oil phase is selected from any one of cyclohexane and n-heptane or a mixture of the two in any proportion.

9. A method for applying the concrete mixture water molecule migration inhibitor prepared by the method according to any one of claims 5 to 8, characterized in that: The concrete mixture water molecule migration inhibitor is applied to the concrete mixture, and its addition amount is 0.01-0.10% of the mass of the cementitious material.